2019
DOI: 10.3390/ijerph16244913
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a School-Based Anxiety Prevention Program among Primary School Children

Abstract: Anxiety is one of the most common mental health disorders in childhood, and children with anxiety have an increased risk of psychiatric disorders during adulthood. This study aimed to evaluate the effectiveness of a school-based anxiety prevention program for reducing anxiety among primary school students relative to a school-as-usual control group. Secondary to this, the current study aimed to examine the effect of a school-based prevention program on worry coping skills and self-esteem. A two-group parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…These findings on reduced anxiety levels among adolescents following health education intervention were supported by previous international RCT studies [37][38][39]. The findings of this study were consistent with the most similar parallel cluster RCT study in Malaysia, which analysed the effect of health education on reducing anxiety among school-aged students at immediately post-intervention and three-month follow-up [40]. Their study proved that a relatively short health education intervention period (four weeks) without a booster programme was significantly effective in reducing anxiety scores among students.…”
Section: Discussionsupporting
confidence: 90%
“…These findings on reduced anxiety levels among adolescents following health education intervention were supported by previous international RCT studies [37][38][39]. The findings of this study were consistent with the most similar parallel cluster RCT study in Malaysia, which analysed the effect of health education on reducing anxiety among school-aged students at immediately post-intervention and three-month follow-up [40]. Their study proved that a relatively short health education intervention period (four weeks) without a booster programme was significantly effective in reducing anxiety scores among students.…”
Section: Discussionsupporting
confidence: 90%
“…Thirdly, similar to what Johnstone et al (2018) reported in their review, Burke et al (2017) explained how ineffective were programs designed to reduce anxiety in children. However, this finding was contradicted by Ab Ghaffar et al (2019) study, in which a school-based anxiety program effectively reduced anxiety in participating children.…”
Section: Discussionmentioning
confidence: 92%
“…Interventions evaluated were: Cognitive behavioral therapy (CBT) (N = 12-27.90%) (24-27, 29-32, 34, 41, 44, 45), CBT combined with another intervention (N = 2-4.65%) (31,58), Psychoeducation (N = 13-30.23%) (28, 29,33,37,41,50,51,56,57,[59][60][61][62], Neurocognitive (N = 5-11.62%) (34,37,40,54), Narrative psychotherapy (N = 7-16.27%) (35,38,39,(46)(47)(48)55), Yoga/Meditation (N = 4-10%) (23,31,42,49). Table 2 shows the synthesis of the studies included in the systematic review.…”
Section: Key Characteristics Of Included Studiesmentioning
confidence: 99%
“…Table 3 shows the synthesis of the studies included in the systematic review and the risk of bias. There were 7 studies (17.94%) on ADHD (23,36,37,39,42,53,61) (25,30,31,51,59,60,62).…”
Section: Key Characteristics Of Included Studiesmentioning
confidence: 99%